Type 2 diabetes and risk of major cardiovascular events in peripheral artery disease versus coronary artery disease patients. (14th October 2021) - Saely, C H; Vonbank, A; Larcher, B; Mader, A; Maechler, M; Sprenger, L; Mutschlechner, B; Benda, M; Leiherer, A; Muendlein, A; Drexel, H
Abstract:  : The prevalence of type 2 diabetes (T2DM) is higher in peripheral artery disease (PAD) than in coronary artery disease (CAD) patients, and PAD overall confers higher cardiovascular risk than CAD. The purpose of this study was to investigate how the incidence of major cardiovascular events compares between PAD and CAD patients when analyses are stratified by the presence of type 2 diabetes (T2DM). We prospectively recorded major cardiovascular events and death over 10.0±4.7 years in 923 patients with stable CAD, of whom 26.7% had T2DM and in 292 patients with PAD, of whom 42.1% had T2DM. Four groups were analyzed: CAD patients without diabetes (CAD/T2DM-; n=677), CAD patients with T2DM (CAD/T2DM+; n=246), PAD patients without diabetes (PAD/T2DM-; n=169) and PAD patients with T2DM (PAD/T2DM+; n=123). When compared to the incidence of MACE in CAD+/T2DM- patients (25.1%), it was significantly higher in CAD+/T2DM+ patients (35.4%; p<0.001), in PAD+/T2DM- patients (30.2%; p=0.022) and in PAD+/T2DM+ patients (47.2%; p<0.001). Patients with both PAD and T2DM in turn were at a higher risk than CAD+/T2DM+ or PAD+/T2DM- patients (p=0.001 and p<0.001, respectively). The incidence of MACE did not differ significantly between PAD+/T2DM- and CAD+/T2DM+ patients (p=0.413). Compared to patients with CAD, Cox regression analyses after multivariate adjustment showed an adjusted hazard ratio of 1.46 [1.14–1.87], p=0.002 for the presence of PAD. Conversely, T2DM increased the risk of MACE after multivariate adjustment in CAD and PAD patients (adjusted HR 1.58 [1.27–1.98], p<0.001). In conclusion, our data show that T2DM and the presence of PAD are mutually independent predictors of MACE. Patients with both PAD and T2DM are at an exceedingly high risk of MACE. FUNDunding Acknowledgement: Type of funding sources: None.